A Novel In Vitro Model for Studying Quiescence and Activation of Primary Isolated Human Myoblasts - Sellathurai, Jeeva (Public Library of Science, 2013)
Skeletal muscle stem cells, satellite cells, are normally quiescent but become activated upon muscle injury. Recruitment of resident satellite cells may be a useful strategy for treatment of muscle disorders, but little is known about gene expression in quiescent human satellite cells or the mechanisms involved in their early activation. We have developed a method to induce quiescence in purified primary human myoblasts isolated from healthy individuals. Analysis of the resting state showed absence of BrdU incorporation and lack of KI67 expression, as well as the extended kinetics during synchronous reactivation into the cell cycle, confirming arrest in the G(0) phase. Reactivation studies showed that the majority (>95%) of the G(0) arrested cells were able to re-enter the cell cycle, confirming reversibility of arrest. Furthermore, a panel of important myogenic factors showed expression patterns similar to those reported for mouse satellite cells in G(0), reactivated and differentiated cultures, supporting the applicability of the human model. In addition, gene expression profiling showed that a large number of genes (4598) were differentially expressed in cells activated from G0 compared to long term exponentially proliferating cultures normally used for in vitro studies. Human myoblasts cultured through many passages inevitably consist of a mixture of proliferating and non-proliferating cells, while cells activated from G(0) are in a synchronously proliferating phase, and therefore may be a better model for in vivo proliferating satellite cells. Furthermore, the temporal propagation of proliferation in these synchronized cultures resembles the pattern seen in vivo during regeneration. We therefore present this culture model as a useful and novel condition for molecular analysis of quiescence and reactivation of human myoblasts.